The effect of treating method of pithed pheasant on the content of biogenic amines in the meat during the course of storage - Hutarova, Z; Vecerek, V; Steinhauserova, I; Marsalek, P; Borilova, G; Forejtek, P (Poultry science, 2013)
The study monitored the effect of various methods of treating pheasant carcasses after killing on the hygienic quality of the venison. Pithed pheasants treated by evisceration (n = 60), drawing (n = 60), or left untreated (n = 60) were stored for a period of 21 d at temperatures of 0, 7, and 15°C. For determination of biogenic amines, samples of breast and thigh muscles were taken on d 1, 7, 14, and 21 after killing of the pheasants. Biogenic amines were separated by reverse-phase liquid chromatography and consequently detected by tandem mass spectrometry. The sum of determined biogenic amine concentrations (cadaverine, putrescine, histamine, tyramine, tryptamine, phenylethylamine) was compared with the value of the index for meat of high hygienic quality (5 mg/kg). At a storage temperature of 0°C, the sum of biogenic amine concentrations did not exceed the value of 5 mg/kg in either breast or thigh muscle at any time during the storage period in untreated and drawn pheasants, and for a period of 14 d in eviscerated pheasants. At a storage temperature of 7°C, values lower than the limit of 5 mg/kg were recorded throughout the storage period in untreated pheasants, for a period of 14 d of storage in drawn pheasants, and for a period of just 7 d of storage in eviscerated birds. At the highest storage temperature (15°C), a value of 5 mg/kg was exceeded in eviscerated and untreated pheasants during the course of the first week of storage, and in drawn pheasants after the first week of storage. Our results indicate that the most suitable method of treatment to ensure high hygienic quality of the meat (assessed according to concentration of biogenic amines) for the longest period during the storage of pithed pheasants is to leave the pheasant carcasses untreated, followed by the drawing, with the least suitable method being the widely recommended method of evisceration.
Keywords: časové faktory; Galliformes; Animals; Biogenic Amines; Time Factors; biogenní aminy; mužské pohlaví; Male; skladování potravin; zvířata; Food Storage; Meat; maso